Effects of COVID-19 on non-communicable diseases and reproductive health services in a district hospital of Nepal - Rajan Ghimire; Sugat Adhikari (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
COVID-19 pandemic has an impact on the socio-economic, cultural, and health of people. There is increased morbidity if a patient with comorbidities (hypertension, diabetes) is infected with SARS-CoV 2. On the other hand, there are increased complications related to hypertension, diabetes, and unwanted pregnancies during this pandemic. We did a retrospective study in a district hospital in Nepal to see this effect. We found that there was an increased incidence of uncontrolled diabetes, hypertension, and safe abortions. So while making plans for overall health during this pandemics, proper management of non-communicable diseases and reproductive health services should be considered.